ARTIFICIAL INTELLIGENCE AND THE TRANSFORMATION OF DIGITAL SEARCH ECOSYSTEMS: A BIBLIOMETRIC REVIEW OF INFORMATION LITERACY AND USER BEHAVIOR - Shafira Nanda Widjaya; Yunus Winoto; Santi Susanti (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2025)
This study presents a bibliometric review of the intersection between artificial intelligence (AI), information literacy, and user behavior in digital search ecosystems. The rapid growth of AI technologies, particularly in machine learning and deep learning, has significantly transformed digital search environments, affecting how users seek and process information. Despite the advancements, there is a growing concern over the widening digital literacy gap, particularly in countries undergoing digital transitions like Indonesia, where individuals with limited digital skills struggle to navigate AI-powered search systems. This review analyzes scholarly publications from 2014 to 2024, identifying publication trends, thematic focuses, and gaps in research related to AI-mediated information retrieval. The study reveals that while AI-driven technologies such as large language models and recommendation systems have reshaped search ecosystems, little attention has been given to understanding how users, especially those with low information literacy, interact with these systems. The findings underscore the need for targeted interventions to improve digital and AI literacy, particularly in educational and public sectors. Future research should explore the social and cultural implications of AI in information access, focusing on diverse user groups and ethical considerations. This study contributes to both theoretical and practical knowledge by mapping the development of AI research and identifying areas requiring further exploration to ensure equitable access to information.